2017
DOI: 10.1016/j.jjcc.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the clinical significance of single cuff-based arterial stiffness parameters with that of the commonly used parameters

Abstract: In patients with cardiovascular diseases or cardiovascular risk factors, the new simple markers and the commonly used markers are not interchangeable for assessing vascular damage and/or cardiovascular risk. Further study is proposed to examine whether AVI is higher in subjects with cardiovascular disease than in those without a history of cardiovascular disease. Similar to the case for the commonly used markers, age and the blood pressure significantly influenced both the new markers; therefore, age and the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 13 publications
3
21
0
Order By: Relevance
“…Age and blood pressure affect the AVI [5]. While age and blood pressure were included as covariates in the analysis model used in this study for adjustments, the present findings need to be confirmed in the elderly, in subjects with hypertension, and also in the general population.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Age and blood pressure affect the AVI [5]. While age and blood pressure were included as covariates in the analysis model used in this study for adjustments, the present findings need to be confirmed in the elderly, in subjects with hypertension, and also in the general population.…”
Section: Discussionmentioning
confidence: 72%
“…Recently, we reported that the AVI was higher in patients admitted for coronary angiography (i.e., subjects suspected to have advanced atherosclerosis, e.g., coronary artery disease) than in those admitted for other reasons than coronary angiography (i.e., subjects not suspected to have advanced atherosclerosis, e.g., arrhythmia) [5]. Hitsumoto [6] reported that the AVI was significantly higher in patients with detectable high-sensitivity troponin T than in those without detectable high-sensitivity troponin T. Sasaki-Nakashima et al [7] reported that the API was significantly and independently associated with both the Framingham Cardiovascular Risk Score and the Suita Score.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The AVE-1500 (Shisei Datum, Tokyo, Japan) is a newly developed device that can non-invasively evaluate arterial stiffness and endothelial dysfunction of the central arteries (arterial velocity pulse index [AVI]) and peripheral arteries (arterial pressure volume index [API]) using a cuff-oscillometric technique in a single blood pressure measurement. We previously reported that the AVI and API are significantly correlated but showed different CV implications 6,7) ; conversely, other studies have reported various implications of these indexes for CV risks [8][9][10][11] . Additionally, both the severity of coronary heart disease and complexity of the coronary artery in affected patients are significantly correlated with API 7) .…”
Section: Introductionmentioning
confidence: 76%